Pharmacodynamic monitoring by residual NFAT-regulated gene expression in stable pediatric liver transplant recipients - Billing, Heiko; Breil, Thomas; Schmidt, Jan; Tönshoff, Burkhard; Schmitt, Claus P.; Giese, Thomas; Engelmann, Guido (Pediatric transplantation, 2012)
Billing H, Breil T, Schmidt J, Tönshoff B, Schmitt C, Giese T, Engelmann G. Pharmacodynamic monitoring by residual NFAT-regulated gene expression in stable pediatric liver transplant recipients. Pediatr Transplantation 2012: 16: 187-194. © 2012 John Wiley & Sons A/S. Abstract: Pharmacokinetic monitoring of CNI is unsatisfactory, because at comparable CNI blood concentrations frequency and severity of adverse effects vary considerably among individual patients. Determining the RGE of NFAT-regulated genes in leukocytes is a new pharmacodynamic approach to measure directly the functional consequences of calcineurin inhibition in T-lymphocytes. We compared clinical outcome parameters and RGE of activated T-cells after pLtx. We measured prospectively RGE of NFAT regulated genes in 33 pLTX recipients in the maintenance period after pLTX. CsA-treated patients with recurrent infections had significantly lower RGE rates (27%) than children without recurrent infections (50%; p = 0.04), whereas pharmacokinetic parameters of CsA and the concomitant immunosuppressive therapy were comparable between both groups. In patients on tacrolimus-based IS therapy NFAT RGE was only slightly reduced (90%). Pharmacodynamic monitoring of CsA by measurement of RGE in T-lymphocytes has the potential to identify over-immunosuppressed pediatric liver transplant recipients on a CsA-based IS therapy, while in children on low-dose tacrolimus therapy, RGE measurement does not provide additional clinically useful information.
Gesehen am 26.07.2018